Pengaruh Penggunaan Instagram Terhadap Keberhasilan Promosi di Objek Wisata Kali Bening Jepara Jawa Tengah - Nadya Amelia Pratiwi; Danang Prasetyo; Fitri Puji Lestari (CV. Kurnia Grup, 2024)
The purpose of this research is to determine the effect of using Instagram on the success of promotions at the Kali Bening Jepara tourist attraction. This research was conducted on tourists and managers. This research uses descriptive quantitative methods. The number of samples in this study was 97 respondents. Data collection was obtained from observation, documentation and the results of distributing questionnaires to tourists and managers of the Kali Bening Jepara tourist attraction. Data analysis in this study used simple linear regression analysis. The results of simple linear regression analysis show that the Instagram usage variable has a positive and significant effect on promotional success.